Structure and Electrochemical Behavior of Minor Mn-Doped Olivine LiMnxFe1−xPO4 - Le Thanh Nguyen Huynh; Pham Phuong Nam Le; Viet Dung Trinh; Hong Huy Tran; Van Man Tran; My Loan Phung Le (Journal of Chemistry)
In the recent years, olivine LiFePO4 has been considered as a prospective cathode material for lithium-ion batteries. However, low conductivity is an obstacle to the commercialization of LiFePO4; doping the transition metal such as Mn and Ni is one of the solutions for this issue. This work aimed to synthesize the Mn-doped olivines LiMnxFe1−xPO4 at low content of Mn (x = 0.1, 0.2) via the hydrothermal route followed by pyrolyzed carbon coating. The synthesized olivines were well crystallized in olivine structure, with larger lattice parameters compared with LiFePO4. The EXD and TGA results confirmed the coated carbon of 4.14% for LiMn0.1Fe0.9PO4 and 6.86% for LiMn0.2Fe0.8PO4. Both of Mn-doped olivines showed higher diffusion coefficients of Li+ intercalation than those of LiFePO4 that led a good performance in the cycling test. LiMn0.2Fe0.8PO4 exhibited a higher specific capacity (160 mAh/g) than LiMn0.1Fe0.9PO4 (155 mAh/g), and the Mn content is beneficial for the cycling performance as well as ionic conductivity.